Sentido, sujeto y formación. - Páez, Alfonso Cárdenas (Enunciación)
This paper explores the pedagogical implications of Mikhail Bakhtin's theory around three fundamental notions: meaning, subject, and education. Based on a critique of modern conceptions of language and subject as closed and objective entities, it proposes a dialogical, ethical, and evaluative perspective that recognizes the complexity of the educational event. Meaning is understood as a historical, enunciative, and situated construction that manifests itself at the intersection of meanings, values, and ideological accents. In this framework, the subject is not a finished entity, but rather an open, intersubjective, and interobjective configuration that is constituted in relation to the other and the Other--culture--in a process of extraposition and dialogue. From this architecture, education is conceived as an ethically committed practice of meaning, where cognitive, aesthetic, and volitional dimensions are articulated. Understanding, in this context, is not only an intellectual act, but an ethical event that allows the subject to situate themselves, take responsibility, and project themselves into the world. Consequently, a critical pedagogy is proposed that recognizes the word as a means of transformation, difference as a source of meaning, and knowledge as a relational and historical practice. Thus, education ceases to focus on the transmission of content and instead orients itself toward the formation of responsible, heteronomous, and dialogical subjects, capable of inhabiting the world from a situated consciousness that is plural and open to the other.